2011
DOI: 10.1111/j.1553-2712.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Refinement of the Difficult Intravenous Access Score: A Clinical Prediction Rule for Identifying Children With Difficult Intravenous Access

Abstract: Objectives: The difficult intravenous access (DIVA) score, a proportionally weighted four-variable (vein palpability, vein visibility, patient age, and history of prematurity) clinical rule, has been developed to predict failure of intravenous (IV) placement in children. This study sought to externally validate and refine the DIVA score.Methods: Patients undergoing peripheral IV placement by pediatric emergency department (ED) nurses were enrolled. The outcome of interest was defined as failure of cannulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 5 publications
(4 reference statements)
3
131
0
13
Order By: Relevance
“…6 Prior to the study, first attempts success was estimated to be 55–70% and a 15% improvement was determined by experts in the field to be clinically important. 4,5,6 A change of 15% required 134 patients in each group to obtain an alpha of 0.05 (two-sided) and a beta of 0.20. An additional 10% were enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Prior to the study, first attempts success was estimated to be 55–70% and a 15% improvement was determined by experts in the field to be clinically important. 4,5,6 A change of 15% required 134 patients in each group to obtain an alpha of 0.05 (two-sided) and a beta of 0.20. An additional 10% were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 For children in particular, pain experienced during IV placement can result in increased movement and lack of cooperation, making success more difficult. 3 A study of topical lidocaine found improved IV placement success in children was associated with analgesic use suggesting an intervention to decrease pain may increase placement success.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, a recent study by Riker et al [10] has simplified previous multifactorial paediatric prediction rules into a three-factor scoring system without forfeiting accuracy. Predictors in the Riker model are: (1) Vein visible with tourniquet in place.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, these guidelines suggest a pre-emptive use of alternatives (again intraosseous access) in situations where cannulation failure seems likely. However, although predictors for a difficult intravenous access have been investigated for in-hospital settings [8][9][10][11][12], only little data are available on the special environment of prehospital emergency care. In summary, there is a profound lack of evidence to base the above-mentioned prediction of success on anything but one's own gut feeling.…”
Section: Introductionmentioning
confidence: 99%
“…IV placement can be challenging in pediatric patients; the failure rate can reach 47% on the first attempt, and 9% of patients require more than four attempts before peripheral IV access is obtained (2). The data from an emergency department reported a success rate of 67.8% on the first catheterization attempt in pediatric patients (3). Even when interventions such as venous imaging ultrasound are used, two or more attempts are still required for 15% of children to achieve access (4).…”
Section: Introductionmentioning
confidence: 99%